2018
DOI: 10.1016/j.cbpa.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves growth, alters physiological performance and gene expression in common carp (Cyprinus carpio)

Abstract: It has been suggested that induced swimming has the potential to improve the growth performance of fish. We tested this hypothesis by measuring growth, metabolic efficiency and physiological capacity of common carp (Cyprinus carpio). Fish were swum at different exercise regimes: 0.0 (control), 1.5 and 2.5 body lengths per second (BL/s) in 1600 L recirculating raceways for 4 weeks. The results showed a significant increase in weight gain, specific growth rate, improved feed conversion efficiency, and a higher h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Somatic growth in vertebrates is mainly regulated by the hypothalamic-pituitary axis through the growth hormone (GH) and the insulin-like growth factors (IGFs) system [ 17 ], and many authors reviewed its role in fish species [ 18 , 19 , 20 , 21 ]. In gilthead sea bream, changes in the GH-IGFs axis were studied through the seasonal cycle [ 22 ], life stages [ 23 ], nutritional status [ 24 , 25 ], as a response to environmental factors [ 26 , 27 ], or even after several weeks of sustained exercise [ 14 , 28 ]. All these works highlighted the important regulatory functions of those endocrine factors in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic growth in vertebrates is mainly regulated by the hypothalamic-pituitary axis through the growth hormone (GH) and the insulin-like growth factors (IGFs) system [ 17 ], and many authors reviewed its role in fish species [ 18 , 19 , 20 , 21 ]. In gilthead sea bream, changes in the GH-IGFs axis were studied through the seasonal cycle [ 22 ], life stages [ 23 ], nutritional status [ 24 , 25 ], as a response to environmental factors [ 26 , 27 ], or even after several weeks of sustained exercise [ 14 , 28 ]. All these works highlighted the important regulatory functions of those endocrine factors in this species.…”
Section: Introductionmentioning
confidence: 99%
“…This, of course, implies progressively reduced feed efficiency and FCR as swimming speed increases (Kiessling et al, 1994(Kiessling et al, , 2005Khan et al, 2014;Skov et al, 2015; Table 1). It is conceivable, nonetheless, that FCR and growth 'efficiency' are improved in exercised fish compared with those held in still water (Christiansen & Jobling, 1990;Jobling et al, 1993;Shrivastava et al, 2018). Swimming exercise at moderate levels appears to stimulate various regulatory factors that affect feed intake or growth, such as the expression of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) (Barrett & McKeown, 1988;Blasco et al, 2015;Shrivastava et al, 2018) as well as expression of various genes associated with growth processes (Palstra et al, 2010b).…”
Section: Sparus Auratamentioning
confidence: 99%
“…Although it is frequently reported that fish submitted to moderate swimming exercise have higher growth rates than those held in still water or at low currents (e.g. Ibarz et al, 2011; Palstra et al, 2015; Shrivastava et al, 2018), other studies have found that swimming exercise has no, or even negative, effects on growth (e.g. Kiessling et al, 1994; McKenzie et al, 2012; Skov et al, 2015).…”
Section: Exercise and Production: Effects On Growthmentioning
confidence: 99%
“…Reference genes for the relative gene expression analysis were selected based on a two-step selection process. First, the related literature was studied to pinpoint the relevant panel of reference genes for carp [24,[33][34][35]. Second, the RT-qPCR analysis was performed on a full set of cDNA samples to determine the reference genes' quality and stability in the samples from skin mucosa.…”
Section: Reference Genesmentioning
confidence: 99%